2022
DOI: 10.1590/1980-5764-dn-2022-0017
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric symptoms of dementia and caregivers’ burden: a study among Indian caregivers

Abstract: Dementia is considered a most serious and disabling condition, affecting both the individual suffering from it and their caregiver. Objective: The study aimed to evaluate the relationship between neuropsychiatric problems of dementia and caregiver burden. Methods: A total of 138 caregivers of people with dementia participated in this cross-sectional study. The caregivers completed the questionnaires containing sociodemographic information as well as neuropsychiatric problems of dementia and caregiver burden.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Those specific characteristics may include important behavioral changes in the most severe forms of the disease, such as the total loss of self-feeding and hydration capacity. As the disease progresses, dependence and the need for a caregiver also increase [ 53 , 54 , 55 , 56 ]. Due to these characteristics, the difficulty in collecting 24-h urine samples is further increased, reinforcing the added value of the results that this study provides.…”
Section: Discussionmentioning
confidence: 99%
“…Those specific characteristics may include important behavioral changes in the most severe forms of the disease, such as the total loss of self-feeding and hydration capacity. As the disease progresses, dependence and the need for a caregiver also increase [ 53 , 54 , 55 , 56 ]. Due to these characteristics, the difficulty in collecting 24-h urine samples is further increased, reinforcing the added value of the results that this study provides.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed that sudden changes in behaviors, anxiety, and delusions contribute to caregiver psychological well-being. This issue is particularly prevalent in Vietnam and other non-WEIRD populations where caregiving responsibilities typically fall on family members (Basu & Mukhopadhyay, 2022; Nguyen et al, 2021). As a result, caregivers often lack the necessary skills to manage TBI rehabilitation and provide adequate care.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to non-TBI groups, caregivers of patients with TBI, including familial and paid caregivers, experienced higher levels of care burden and stress (Basu & Mukhopadhyay, 2022; Curtiss et al, 2000), a higher risk of developing depression and anxiety (Rivera et al, 2007; Tay & Kong, 2020), lower life satisfaction, mood swings, and negative thoughts (Anderson et al, 2002; Kaewphinit et al, 2022). In Asia, where cultural norms prioritize familial value and the outsourcing of caregiving duties is avoided, it is common for family members to bear the caregiving responsibilities for patients with neurological disorders, including TBI (Basu & Mukhopadhyay, 2022; Devi et al, 2020, Kaewphinit et al, 2022). Moreover, due to high costs or the scarcity of care services, families are frequently responsible for rehabilitation and recovery following hospital discharge (Pekerti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, studies during the review period were carried out either in South India [10 ▪▪ ,11,12,13 ▪▪ ] or Eastern India [14 ▪▪ ,15,16 ▪ ,17 ▪▪ ] and mainly in urban settings, highlighting a gap in information about dementia care experience in rural areas and other regions of India. Overall, studies show primary caregivers are typically family members with the majority being women; either the wife, daughter, or daughter-in-law.…”
Section: Methodsmentioning
confidence: 99%